An extant whale barnacle (Cirripedia, Coronulidae) from Holocene deposits of Buenos Aires (Argentina) - Pastorino, Guido (1996)
Fil: Pastorino, Guido. División Paleozoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina